Pengaruh Fitur Aplikasi Tiktok Jharna Bhagwani terhadap Keputusan Penggunaan Produk Make Up - Nurpahmi, Siti; KN, Jamiati (School of Communication - Atma Jaya Catholic University of Indonesia, 2023)
As of the first quarter of 2022, there are 1.39 billion monthly active users of the Tiktok app globally. When compared to a year ago, this number is still rising and now stands at 72.17 percent. It was mentioned that there were still 812 million active monthly users in the first quarter of 2021. Video shows are one of the most popular services offered by the Tiktok program since they can motivate users to create films and offer both fun and knowledge. The goal of this study is to determine and quantify how employing Tiktok Jharna Bhagwani application features affects usage decisions. employing a quantitative strategy and an explanatory survey technique. The sample size for this study is the 255 respondents who follow the Tiktok account @JharnaBhagwani, which is only allowed to contain one post. A sample of 72 respondents was created by applying the slovin technique formula to take the sample. The Simple Random Sampling Technique is employed in the sampling process. employing questionnaires for data collecting and simple linear regression analysis for data analysis. The study's findings indicate that the use of the Tiktok application features has a t count value (13.443) > t table (1.667), and that H 0 is rejected and H 1 is accepted, indicating that there is an impact between the use of the Tiktok application features developed by Jharna Bhagwani and the choice to use cosmetics. The utilization of the Tiktok Jharna Bhagwani Application Features, which is the X variable, has an influence on the Y variable, according to the coefficient of determination results, which had a R square value of 0.72. The decision to use makeup products is impacted by other factors outside of this study for 72% and by other factors for the remaining 28%.